The Effect of Premium Revenue, Underwriting Results, Investment Results, and Risk Based Capital on Income in Insurance Company (Study On Corporate Insurance - The Listed on the Indonesia Stock Exchange) - Wahyuddin; Mauliyana (Yayasan Ahmar Cendekia Indonesia, 2021)
This research is intended to determine how much influence the premium income, underwriting results, investment results, and risk based capital on the profit of insurance companies (a study of insurance companies listed on the Indonesia Stock Exchange). In this study, the technique to collect the form of financial documentation as the data were taken from 11 insurance companies as samples that listed on the Indonesia Stock Exchange in 2017-2019. The multiple linear regression analysis methods use to analyze the data. The results of this study indicate that premium income, underwriting results, investment returns, and Rased Based Capital have a positive and significant effect on profits in insurance companies registered in Indonesia in 2017-2019. It is hoped that insurance companies registered in Indonesia will be able to maintain the value of premium income, underwriting results, and Rased Based Capital in the company, this is so that insurance companies are able to provide more performance for the progress of the company in the future.